ANALISIS KAUSALITAS INFLASI, KETIMPANGAN PENDAPATAN, DAN PERTUMBUHAN EKONOMI DI INDONESIA - Rifki Ihsan; Hasdi Aimon; Alpon Satrianto (Universitas Negeri Padang, 2018)
The aim of this study is to analyze the relationship between Inflation, Income Inequality and Economic Growth in Indonesia. The type of this research is associative and analysisdescriptive. The data used in this reseach is secondary of time series from 1986 to 2016 obtained from Word Bank. Analysis model using the Vector Autoregression (VAR). Theanalysis initially used the Vector Autoregression (VAR), because the stationer variabel on first diferent range, then this study continued byVector Error CorrectionModel (VECM) and Granger Causality Test. The result of this study show (1) There is nocausality between Inflation affects to Income Inequality, (2) There is no causality between Inflation affects to Economic Growth, (3) There is causality in the direction in which Income Inequality affects to Economic Growth. In addition, because of the prevalence of income in Indonesia, this will increase economic growth in Indonesia. Keywords:Inflation, Income Inequality, Economic Growth